2000
DOI: 10.1109/48.855390
|View full text |Cite
|
Sign up to set email alerts
|

An environmental assessment in the Strait of Sicily: measurement and analysis techniques for determining bottom and oceanographic properties

Abstract: Executive Summary:In October 1997, the En Verse 97 shallow water acoustic experiments were jointly conducted by SACLANT Centre, TNO-FEL and DERA off the coast of Sicily, Italy. The primary goal of the experiments was to test rapid environmental assessment (REA) techniques for shallow water. Most of the oceanographic REA methods discussed here are well developed and emphasis in this report is on determining the sea-bed properties through inversion of measured acoustic data. To develop an operational system, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…[3][4][5] Alternatively, geoacoustic inversion methods can be used to estimate more accurate seabed parameters, which are typically the source of greatest environmental uncertainty. Inversions can be done using either transmissions of known wave forms from calibrated sources 6,7 or from sources of opportunity such as loud merchant ships. 7 Other authors have suggested the use of guide sources for mitigating environmental uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Alternatively, geoacoustic inversion methods can be used to estimate more accurate seabed parameters, which are typically the source of greatest environmental uncertainty. Inversions can be done using either transmissions of known wave forms from calibrated sources 6,7 or from sources of opportunity such as loud merchant ships. 7 Other authors have suggested the use of guide sources for mitigating environmental uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…The community has developed many techniques for data association (i.e., finding which measurement is derived from which target) and for tracking maneuvering targets. [2][3][4] On the other hand, on MFP appears to have focused on signal processing 10,19 : the focus is, not unreasonably, on detecting the target. Treatments of combined tracking/MFP systems are not common, but most concentrate on signal processing, with the idea that a "track" is really a sequence or track-segment of detections that make sense from dynamics considerations.…”
Section: Overviewmentioning
confidence: 99%
“…4,5 On the contrary, a VLA configuration is relatively stable and capable of receiving sound fields from all directions and can probe large areas around the VLA with a towed source or multiple sources. [6][7][8][9][10][11] Although there is some computational complexity in propagation modeling, VLA configurations are still effective in range-dependent inversion.…”
Section: Introductionmentioning
confidence: 99%
“…The MF inversion has been successfully applied to estimate bottom characteristics in various shallow water environments. [1][2][3][4][5][6][7][8][9][10][11][12] Actual shallow water environments usually have range variability in seabed properties as well as in bathymetry or ocean sound speed. However, in conventional geoacoustic inversions using a vertical line array ͑VLA͒ and a single source, the geoacoustic properties have been typically assumed to be range independent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation